Preliminary analysis of gamma and neutron irradiation on sand and activated carbon by using SEM, XRD and SAXS - Abu Bakar A.A.; Pauzi A.M.; Mohamed A.A.; Idris F.M.; Yazid H. (Institute of Physics Publishing, 2023)
Activated carbon; Neutrons; Sand; X ray diffraction; Gamma energy; Irradiated samples; Mechanical damages; Morphological analysis; Neutron fluences; Preliminary analysis; Strong correlation; XRD patterns; Neutron irradiation